Emerging Nanoporous Materials for Biomolecule Separation. (25th February 2022) - Song, Yongyang; Bao, Han; Shen, Xinyi; Li, Xiuling; Liang, Xinmiao; Wang, Shutao
Abstract: Biomolecule separation plays a vital role in downstream applications ranging from omics research, structure analysis, and drug purification to clinical diagnosis. Among all existing materials and technologies towards biomolecule separation, nanoporous materials take the leading place. To achieve efficient biomolecule separation, the interface of nanoporous materials is always modified with a monolayer containing specific functional groups. However, the monolayer modification strategy still encounters bottlenecks due to extremely low abundance of target biomolecules, strong interference from high‐abundance background biomolecules, similar characteristics of compounds, unspecific adsorption, et al. Recently, several emerging nanoporous materials, which are prepared without the monolayer modification process, have been reported for high‐efficient, high‐specific, and rapid biomolecule separation. In this review, the authors summarize the emerging nanoporous materials for biomolecule separation, mainly focusing on the design principle and separation performance that are different from classical nanoporous materials. First, the classic design strategy of monolayer modification is discussed and the recent progress with this aspect is introduced. Then, emerging nanoporous materials beyond monolayer modification are introduced. At last, future developments, challenges, and great promise of biomolecule separation nanoporous materials are discussed. Abstract : Biomolecule separation plays a vital role for omics research, structure analysis, drug purification, and clinical diagnosis. Nanoporous materials take the leading place in efficient biomolecule separation. In this review, we summarize the development of emerging nanoporous materials for biomolecule separation with an aspect of monolayer modification and beyond, and discuss their future developments, challenges, and great promise.